Oskrbna središča na Jesenicah - Plevnik, Aljaž (Urbani izziv, 1994)
While preparing the urban master plan for Jesenice, supply centres were identified as an important factor in physical positioning. When determining the character of supply centres the emphasis is on the gravitational hinterland and conditions of supply. In the proposal for locating supply centres three hierarchical ranks where identified, namely, the primary centre, centres of subunits and local centres. Because of the morphologic structure of Jesenice, linear grouping, as another type of supply centres appears.
Keywords: centralna naselja; Jesenice; obmestja; oskrbne dejavnosti; regionalno planiranje; urbanistično planiranje